Insufficient response to mRNA SARS‐CoV‐2 vaccine and high incidence of severe COVID‐19 in kidney transplant recipients during pandemic. Issue 3 (10th December 2021) - Reischig, Tomas; Kacer, Martin; Vlas, Tomas; Drenko, Petr; Kielberger, Lukas; Machova, Jana; Topolcan, Ondrej; Kucera, Radek; Kormunda, Stanislav
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) mRNA vaccination may fail to sufficiently protect transplant recipients against coronavirus disease 2019 (COVID‐19). We retrospectively evaluated COVID‐19 in kidney transplant recipients ( n = 226) after BNT162b2 mRNA vaccine administration. The control group consisted of unvaccinated patients ( n = 194) during the previous pandemic wave. We measured anti‐spike protein immunoglobulin G (IgG) levels and cellular responses, using enzyme‐linked immunosorbent spot assay, in a prospective cohort after vaccination ( n = 31) and recovery from COVID‐19 ( n = 19). COVID‐19 was diagnosed in 37 (16%) vaccinated and 43 (22%) unvaccinated patients. COVID‐19 severity was similar in both groups, with patients exhibiting a comparable need for hospitalization (41% vs. 40%, p = 1.000) and mortality (14% vs. 9%, p = .726). Short posttransplant periods were associated with COVID‐19 after vaccination ( p < .001). Only 5 (16%) patients achieved positive SARS‐CoV‐2 IgG after vaccination, and 17 (89%, p < .001) recovered from COVID‐19 (median IgG levels, 0.6 vs. 52.5 AU/ml, p < .001). A cellular response following vaccination was present in the majority ( n = 22, 71%), with an increase in interleukin 2 secreting T cells ( p < .001). Despite detectable T cell immunity after mRNA vaccination, kidney transplant recipients remained at a high risk of severe COVID‐19. Humoral responses induced by vaccination were significantly lower than that after COVID‐19. Abstract : A two‐dose SARS‐CoV‐2 mRNA vaccination schedule does not induce sufficient humoral response in the majority of kidney transplant recipients who therefore remain at high risk of severe COVID‐19, comparable to unvaccinated patients.